COMPORTAMENTO ÓPTICO E TÉRMICO EM FUNÇÃO DA ESTRUTURA DO SISTEMA VÍTREO TeO2-Li2O-ZnO - Piazzetta, Rubyan Lucas Santos (2015)
This work studied tellurite glasses in a ternary system with the TeO2-Li2O-ZnO composition, divided in three groups with 10%, 15% and 20%mol Li2O fixed. For this study, was made the replacement of known TeO2 network former by ZnO. It used the Differential Scanning Calorimetry (DSC), optical absorption in ultraviolet-visible region (UV-VIS), Raman spectroscopy, Fourier transform infrared (FTIR), linear refractive index (n0) measurement and instrumented nanoindentation. The samples were prepared by melt quenching method in the bulk form. DSC results showed that the glass transition temperature (TG) virtually no change in the glass systems, while that there was an increase in the glass stability due to exchange of TeO2 by ZnO especially for 10 and 15% mol Li2O groups. By continuing, the UV-VIS results indicated a gradual increase in the band gap energy which was calculated by Urbach rule; this increased energy as TeO2 was replaced by ZnO, can also be seen as a blue shift. These same results were confirmed by a structural change seen by Raman spectroscopy: with the increased of ZnO, the vibrational modes located at 450 e 659 cm-1 which incorporate trigonal bipyramids of TeO4 are gradually replaced by vibrational modes at 735-760 cm-1 referred the creation of Zn2Te3O8 units. This behavior by Raman spectroscopy is also confirmed by the FTIR results with increased intensity of peaks related to vibrational modes of ZnO molecules. Therefore, it is verified that the addition of ZnO in the system has the property to decrease the amount of NBOs, which in turn decreases the polarizability of the oxide ion of the system and increases the band gap energy. Lastly, the increase in the band gap values and, Raman and DSC results showed that this glassy system acquires considerable glass stability, has good transmittance in the ultraviolet and visible regions, and thus appears as a promising candidate for host ions optically active.